The Effectiveness of Implementation of Online Lectures on Student Satisfaction in Higher Education Institutions (Case Study of the President University) - Yeni Fajrin; Adhi Setyo Santoso (International Journal of Business Studies, 2021)
This study aims to identify and obtain information about the effectiveness of the implementation of online lectures during the COVID-19 pandemic at Higher Education Institutions, especially President University. Data was collected by looking at the results of student satisfaction assessments of lecturers during the teaching and learning process, namely in the PUIS (President University Information System) system in the "Lecturing Evaluation" menu. The research used quantitative methods and data analysis used SPSS version 21 software. After the data were analyzed, the researchers conducted online interviews with 12 (twelve) lecturers. The results of this study are that there is a significant difference in satisfaction between offline and online lectures, namely, when offline class students can get knowledge directly without any technical constraints and face-to-face teaching and learning process there are values ​​that can be taken such as the process of social, cultural, ethical maturity. and morals that can only be found in the area of ​​education. In contrast to online lectures, apart from technical problems such as the unsupported internet, online classes also make students lose motivation to study because no chemistry can be built. There are different characteristics in each faculty, this is a challenge for lecturers to explore their abilities and provide new knowledge, and of course, it can be well accepted by students. Online classes will run more effectively if both lecturers and students live it with a sense of responsibility.